Diamond membrane production: The critical role of radicals in the non-contact electrochemical etching of sp2 carbon. (15th November 2021) - Tully, Joshua J.; Braxton, Emily; Cobb, Samuel J.; Breeze, Ben G.; Markham, Matthew; Newton, Mark E.; Rodriguez, Paramaconi; Macpherson, Julie V.
Abstract: Sub-micrometre single crystal diamond membranes are of huge importance for next generation optical, quantum and electronic device applications. Electrochemical etching has proven a critical step in the production of such membranes. Etching is used to selectively remove a very thin layer of sub-surface sp 2 carbon, prepared by ion implantation in bulk diamond, releasing the diamond membrane. Due to the nanosized dimensions, etching is typically carried out using non-contact electrochemistry in low conductivity solutions (bipolar arrangement) which whilst effective, results in extremely slow etch rates. In this work, a new method of non-contact electrochemical etching is presented which uses high conductivity, high concentration, fully dissociated aqueous electrolytes. Careful choice of the electrolyte anion results in significant improvements in the sp 2 carbon etch rate. In particular, we show both chloride and sulfate electrolytes increase etch rates significantly (up to × 40 for sulfate) compared to our measurements using the current state-of-the-art solutions and methodologies. Electron paramagnetic resonance experiments, recorded after the electrode potential has been switched off, reveal sizeable hydroxyl radical concentrations at timescales > 10 7 longer than their lifetime (≤μs). These measurements highlight the importance of electrochemically initiated, solution chemistry radical generation and regeneration pathways in high concentration sulfate and chloride solutions for nano-etching applications. Graphical abstract: Image 1